2005
DOI: 10.1111/j.1365-2672.2005.02615.x
|View full text |Cite
|
Sign up to set email alerts
|

Air drying optimization of Saccharomyces cerevisiae through its water-glycerol dehydration properties

Abstract: Aims: This study describes the different stages of optimization in an original drying process for yeasts, which allows the retrieval of dried samples of Saccharomyces cerevisiae CBS 1171 with maximum viability. Methods and Results: The process involves the addition of wheat flour to yeast pellets, followed by mixing and then air-drying in a fluidized bed dryer. The sensitivity to the osmotic stress was first studied in a water-glycerol solution and the observed results were then applied to the drying process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
2
27
1
1
Order By: Relevance
“…This observation was later confirmed when the investigation was extended to food environment (Laroche, Fine, & Gervais, 2005). On the other hand, Mille et al (2005) suggested that after severe dehydration (which resulted in a reduced initial a w prior to drying), the drying temperature exhibited even greater importance to the maintenance of cell viability during the drying process. At the range of 8-25°C, microbial cells were mostly sensitive to the osmotic pressure arisen from dehydration during drying.…”
Section: Protective Carrier For An Enhanced Microbial Survivalmentioning
confidence: 76%
See 3 more Smart Citations
“…This observation was later confirmed when the investigation was extended to food environment (Laroche, Fine, & Gervais, 2005). On the other hand, Mille et al (2005) suggested that after severe dehydration (which resulted in a reduced initial a w prior to drying), the drying temperature exhibited even greater importance to the maintenance of cell viability during the drying process. At the range of 8-25°C, microbial cells were mostly sensitive to the osmotic pressure arisen from dehydration during drying.…”
Section: Protective Carrier For An Enhanced Microbial Survivalmentioning
confidence: 76%
“…As to date, some studies have shown promising results, with a cell survival ratio higher than 80% after being convectively dried Mille et al, 2005;Oliveira et al, 2007;Reddy et al, 2009). Vacuum drying of Saccharomyces cerevisiae under optimized conditions was reported to result in a higher viability than freeze drying (Cerrutti, de Huergo, Galvagno, Schebor, & del Pilar Buera, 2000).…”
Section: Thermal Drying For the Dehydration Of Microorganismsmentioning
confidence: 95%
See 2 more Smart Citations
“…Desiccation studies on E. coli and B. thuringiensis have supported the postulation that an increase in tolerance to drying appears to result from an ability of the sugars to lower the phase transition temperature of the membrane [11,12]. Sugars like trehalose and sucrose have also been shown to protect not only the membranes but also intracellular proteins during bacterial drying [13][14][15][16]. Desiccation tolerance of different cell types ranging from microbial pathogens of humans [17] to several varieties of plant species such as rice (Oryza sativa), wild rice (Zizania palustris) [18] and soybean [19] have also been studied and shown to be related to the production of saccharides in response to an external environmental stress.…”
Section: Introductionmentioning
confidence: 99%